2019
DOI: 10.1016/j.progpolymsci.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Transparent polymer nanocomposites: An overview on their synthesis and advanced properties

Abstract: Since the last decade, there has been an increasing demand for the design of more advanced functional materials. The integration of inorganic nanoparticles to polymer matrices is a powerful tool to confer their fascinating and complementary properties to the polymer materials. Among the different polymer nanocomposites, transparent nanocomposites are of particular interest due to their significance in a wide range of applications. To achieve a high level of transparency in the nanocomposites, it is necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(165 citation statements)
references
References 247 publications
(397 reference statements)
1
147
0
Order By: Relevance
“…These specimens exhibit high transparence and low haze. It has been well known that the transparency depends crucially on the crystal morphologies in crystalline polymers . In this work, however, the crystallinity of PLLA is very low (Table S3, Supporting Information) in both neat PLLA and PVDF/PLLA blend.…”
Section: Methodsmentioning
confidence: 74%
“…These specimens exhibit high transparence and low haze. It has been well known that the transparency depends crucially on the crystal morphologies in crystalline polymers . In this work, however, the crystallinity of PLLA is very low (Table S3, Supporting Information) in both neat PLLA and PVDF/PLLA blend.…”
Section: Methodsmentioning
confidence: 74%
“…The fillers with nanoscaled size can severely alter the physical traits of the polymeric matrix, permitting the engineering of healed biomaterials that individual materials cannot achieve. The nanomaterials possess an extensive high surface area, compared to conventional microsized fillers, which can generate a strong interface with polymer matrix, suggesting healed mechanical characteristics, while sustaining biocompatibility that affects protein adsorption, cell attachment, proliferation, migration, and differentiation for new tissue formation [109,114].…”
Section: Gum-based Nanocompositesmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] However, the construction of hybrid interfaces would not only affect adhesion, but also offer the possibility to impart new properties, such as enhanced conductivity, improved toughness, and stored active moieties as self-healing agents or bactericidal compounds. [10,12] Recent studies have shown the capability of developing functional materials through the incorporation of thin films on reinforcing agents' surface by using the layer-by-layer (LBL) deposition method. [13][14][15][16] In this work, polypropylene composites with hybrid interface were produced by alternatively depositing two polymers on the glass fiber (GF) surface, poly(diallyldimethylammonium chloride) (PDDA) and poly (sodium 4-styrenesulfonate) (PSS) containing oxidized multiwalled carbon nanotubes (MWCNT-COOH), via the LBL method.…”
Section: Introductionmentioning
confidence: 99%